Swelling‐induced Mechanochromism in Multinetwork Polymers. (12th January 2023) - Watabe, Takuma; Otsuka, Hideyuki
Abstract: We report a novel and versatile approach to achieving swelling‐induced mechanochemistry using a multinetwork (MN) strategy that enables polymer networks to repeatedly swell with monomers and solvents. The isotropic expansion of the first network (FN) provides sufficient force to drive the mechanochemical scission of a radical‐based mechanophore, difluorenylsuccinonitrile (DFSN). Although prompt recombination generally occurs in such highly mobile environments, the resulting pink radicals are kinetically stabilized in the gels, probably due to limited diffusion in the extended polymer chains. Moreover, the DFSN embedded in the isotropically strained chain exhibits increased thermal reactivity, which can be reasonably explained by an entropic contribution of the FN to the dissociation. The utility of the MN polymers is demonstrated not only in terms of swelling‐force‐induced network modification, but also in the context of tunable reactivity of the dissociative unit through proper design of the hierarchical network architecture. Abstract : Swelling‐force‐induced mechanochemical reactions were observed in multinetwork polymers. Sequential swelling of network polymers stretches the network strands, and finally induces selective mechanical scission events at the difluorenylsuccinonitrile (DFSN) mechano‐responsive units, which generate air‐stable radicals with pink color. The increased thermal reactivity of DFSN and kinetic stability of the resulting radicals were also discovered.